Evaluation of a New (1)H/(31)P Dual-Tuned Birdcage Coil for (31)P Spectroscopy - Potter, WM (2013)
We introduce a new dual-tuned Hydrogen/Phosphorus ((1)H/(31)P) birdcage coil, referred to as split birdcage coil, and evaluate its performance using both simulations and magnetic resonance (MR) experiments on a 3 T MR scanner. The proposed coil simplifies the practical matters of tuning and matching, which makes the coil easily reproducible. Simulations were run with the Finite Difference in Time Domain (FDTD) method to evaluate the sensitivity and homogeneity of the magnetic field generated by the proposed (1)H coils. Following simulations, MR experiments were conducted using both a phantom and human thigh to compare the proposed design with a currently available commercial dual-tuned flexible surface coil, referred to as flex surface coil, for signal to noise ratio (SNR) as well as homogeneity for the (31)P coil. At regions deep within the human thigh, the split birdcage coil was able to acquire spectroscopic signal with a higher average SNR than the flex surface coil. For all regions except those close to the flex surface coil, the split birdcage coil matched or exceeded the performance of the flex surface coil.